Growth Performance of Jaffarabadi buffalo in an Organized Herd in North Saurashtra region of Gujarat (Indian Journal of Animal Production and Management, 2024)
Present study deals with growth performance of Jaffarabadi buffalo calves (N=53) born and raised  at Bull Mother Farm, Kamdhenu University, Amreli which is located in North Saurashtra agro-climatic  region of Gujarat. Overall birth weight in Jaffarabadi buffalo calves was 35.01 ± 0.69 kg which was  significantly higher (9.92 %) in male calves (P, 0.016). Irrespective of sex, the Jaffarabadi buffalo  calves weighed 81.76 ± 2.15, 126.40 ± 4.18 and 172.00 ± 6.37 kg at 3, 6 and 12 months of age,  respectively. The Jaffarabadi buffalo heifers attained 395.44 ± 19.80 kg body weight at 2 years of  age, which was higher than the optimum/ desired breedable body (about 375 kg). The average daily  body weight gain from birth to 3 month growth phase was 516.98 ± 24.65 gm/day. In growth phases  during 3 to 12 months of age, the average daily body weight gains were almost similar, 495.67 to  498.63 gm/day. Relative body weight gain, irrespective of sex, was maximum of 136.07 % in the birth  to 3 month age group, followed by 54.55 % in the 3 to 6 month age group. The findings indicated that  due care of the Jaffarabadi buffalo calves, especially during birth to 3 month age, is utmost important  to explore their growth potential as relative weight gain of calves during this phase is maximum  (136.07 %) for attaining early breedable weight and in turn, reducing age at first calving.
Keywords: Jaffarabadi buffalo; absolute growth rate; body weight gain; relative growth